The Irr and RirA proteins participate in a complex regulatory circuit and act in concert to modulate bacterioferritin expression in Ensifer meliloti 1021 - Costa, Daniela (2017)
In this work we found that the bfr gene of the rhizobial species Ensifer meliloti, encoding a bacterioferritin iron storage protein, is involved in iron homeostasis and the oxidative stress response. This gene is located downstream of and overlapping the smc03787 open reading frame (ORF). No well-predicted RirA or Irr boxes were found in the region immediately upstream of the bfr gene although two presumptive RirA boxes and one presumptive Irr box were present in the putative promoter of smc03787. We demonstrate that bfr gene expression is enhanced under iron-sufficient conditions and that Irr and RirA modulate this expression. The pattern of bfr gene expression as well as the response to Irr and RirA is inversely correlated to that of smc03787. Moreover, our results suggest that the small RNA SmelC759 participates in RirA- and Irr-mediated regulation of bfr expression and that additional unknown factors are involved in iron-dependent regulation.